Immunogenicity and Safety of the Human Papillomavirus 6, 11, 16, 18 Vaccine in HIV-Infected Young Women - Kahn, Jessica A. (Oxford University Press, 2013)
BACKGROUND: The objective of this study was to determine whether the 3-dose quadrivalent human papillomavirus (HPV) vaccine series (HPV-6, -11, -16, -18) is immunogenic and safe in young women infected with human immunodeficiency virus (HIV). METHODS: We enrolled 99 women aged 16–23 years in a phase 2, open-label, multicenter trial, conducted from 2008 to 2011 by the Adolescent Medicine Trials Network for HIV/AIDS Interventions. Outcome measures were immunogenicity 4 weeks after dose 3, measured by (1) geometric mean titers (GMTs) and (2) seroconversion rates for HPV-6, -11, -16, and -18, among those seronegative and HPV DNA negative for each type. Immune responses were compared to those of a historical comparison group of HIV-negative women (n = 267) using univariate methods. Clinical and laboratory adverse events were assessed after each dose. RESULTS: The mean age of subjects was 21.4 years; 80% were non-Hispanic black, 69 were not taking antiretroviral therapy (ART), and 30 were taking ART. No differences in GMTs were noted among participants taking ART vs the comparison group, but GMTs were lower in participants not taking ART vs the comparison group for HPV-16 (2393 vs 3892 milli-Merck units per milliliter [mMU/mL], P = .012) and HPV-18 (463 vs 801 mMU/mL, P = .003). Seroconversion rates were 100% for HPV-6, -11, -16, and -18 among participants taking ART. Rates ranged from 92.3% (for HPV-18) to 100.0% (for HPV-6) among participants not taking ART. One severe adverse event (fatigue) was noted. CONCLUSIONS: In a sample of HIV-infected women who were HPV DNA and HPV seronegative, immune responses to HPV vaccination were generally robust and the vaccine was well tolerated. CLINICAL TRIALS REGISTRATION: NCT00710593.